Patterns of Cardiovascular Diseases in Covid-19 Patients Admitted to Tertiary Cardiac Care Centre - Jawad Abbas, Arjan Kumar, Narindar Kumar, Syed Dilbahar Ali Shah, Arshad Ali Shah, Iftikhar Ali Shah, (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aim: Globally public health has been drastically affected by the Coronavirus disease (COVID-19) pandemic. There is a scarcity of data regarding risk factors, cardiac injury, and the treatment of cardiovascular disease associated with coronavirus disease. The present study aimed to assess the pattern of cardiovascular disease in COVID-19 patients referred to Tertiary Care Hospital. Methodology: This retrospective study was conducted on 446 adult patients with new-onset or existing cardiovascular disease patients at the department of Cardiology, PNS Shifa hospital Karachi during the period from February 2021 to July 2021.Demographic details, physical examination, comorbid conditions, and laboratory findings were used for data collection from the patient’s admission file. All the patients above 18 years and positively diagnosed with COVID-19 infections through rapid antigen test were enrolled and admitted with cardiovascular disease. The clinical features, chest X-ray, echocardiography, biochemical parameters, and electrocardiogram (ECG) were analyzed for each individual. Congenital heart disease,coronary artery disease, cardiomyopathy, heart failure, arrhythmias, peripheral arterial disease, and myocarditis were different cardiovascular diseases. Statistical analysis was carried out in SPSS version 23. Results: Of the total 446 cardiovascular disease patients, about 334 (74.9%) were male and 112 (25.1%) were females. The overall mean age was 52.82±10.62 years. Out of 446 CVDs patients, the incidence of preexisting and new cardiovascular disease was 225 (50.4%) and 221 (49.5%) respectively. Acute coronary syndrome was the prevalent (50.7%) cardiovascular manifestation followed by elevation myocardial infarction. The incidence of myocarditis, Rhythm and conduction abnormalities was 45 (10.1%) and 126 (28.3%) respectively. QT prolongation and hospital mortality was seen in 45 (10.1%) and 85 (19.1%) respectively. The prevalence of pre-existing cardiovascular disease, atrial fibrillation, cardiogenic shock, and renal failure were predominantly higher in mortality group compared to survival group. Conclusion: Our study found acute coronary syndrome was the prevalent cardiovascular disease. Elevated serum ferritin, lymphopenia, advanced age, cardiogenic shock, lower haemoglobin, renal failure, pre-existing heart failure, and leukocytosis were significantly related to cardiovascular disease increased mortality.